Can height and weight of the patient predict the tibial footprint dimensions of anterior cruciate ligament on MRI: an observational study - Panduranga, Bangalore Venkataswamy; Mahendranath; Dyapur, Ningaraj; Janardhan, Shashank; Kumar, Rati Ranjan; Ganesan, Prabhu Vignesh M. (International Journal of Research in Orthopaedics, 2025)
Background: Anterior cruciate ligament (ACL) reconstruction techniques are increasingly individualized based on patient-specific anatomy. Preoperative knowledge of ACL dimensions guides surgical planning, particularly regarding single versus double-bundle reconstruction. This study aimed to evaluate ACL tibial footprint dimensions in a South Indian population and investigate their correlation with patient anthropometric measures. Methods: This retrospective observational study analyzed MRI scans of 78 patients (41 males, 37 females) with intact ACL who presented with knee pain at a tertiary care teaching hospital in South India between January 2023 and April 2025. ACL tibial footprint length and width were measured on MRI. Correlation and regression analyses were performed to investigate relationships between ACL dimensions and patient height, weight, age and gender. Results: The mean ACL tibial footprint length and width were 13.7±1.8 mm and 11.5±1.4 mm, respectively. Height demonstrated a strong positive correlation with ACL length (r=0.68, p<0.001) and a moderate correlation with ACL width (r=0.52, p<0.001). In multivariable analysis, height remained the strongest independent predictor of ACL length (standardized β=0.53, p<0.001), while weight (β=0.04, p=0.687) and age (β=0.03, p=0.749) showed no significant independent association. For every 1 cm increase in height, ACL length increased by 0.182 mm (95% CI: 0.140-0.224). Gender differences in ACL dimensions were significant but partially attributable to height differences. Overall, 60.3% of participants had ACL length <14 mm, with a significantly higher proportion among females (83.8%) compared to males (39.0%). Conclusions: Height is a strong predictor of ACL tibial footprint dimensions in South Indian patients, explaining 46% of the variability in ACL footprint length. Patient height could serve as a simple clinical predictor of ACL footprint dimensions when advanced imaging is not readily available, potentially guiding surgical decision-making regarding reconstruction technique.